2020
DOI: 10.1021/acs.jafc.9b08252
|View full text |Cite
|
Sign up to set email alerts
|

Neuroprotection by Walnut-Derived Peptides through Autophagy Promotion via Akt/mTOR Signaling Pathway against Oxidative Stress in PC12 Cells

Abstract: Natural-derived peptides are effective substances in attenuating oxidative stress. However, their specific mechanisms have not been fully elucidated, especially in peptide-mediated autophagy. In the present study, TWLPLPR, YVLLPSPK, and KVPPLLY, novel peptides from Juglans mandshurica Maxim, prevented reactive oxygen species (ROS) production, elevated glutathione peroxidase (GSH-Px) activity and adenosine 5′-triphosphate (ATP) levels, and ameliorated apoptosis in Aβ25–35 (at a concentration of 50 μM for 24 h)-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
40
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 54 publications
(40 citation statements)
references
References 41 publications
0
40
0
Order By: Relevance
“…Therefore, these results suggested that YVLLPSPK might relieve the learning and memory impairment in scopolamine-induced mice by suppressing oxidative stress through the amelioration of mitochondrial dysfunctions in hippocampal tissues. In a previous study, we investigated whether YVLLPSPK could play a role in reducing oxidative stress through autophagy in Aβ 25–35 -induced PC12 cells . On the basis of these results, we speculated that YVLLPSPK might modulate the mitochondrial function by promoting mitophagy to ameliorate scopolamine-induced cognitive deficiencies in mice.…”
Section: Results and Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Therefore, these results suggested that YVLLPSPK might relieve the learning and memory impairment in scopolamine-induced mice by suppressing oxidative stress through the amelioration of mitochondrial dysfunctions in hippocampal tissues. In a previous study, we investigated whether YVLLPSPK could play a role in reducing oxidative stress through autophagy in Aβ 25–35 -induced PC12 cells . On the basis of these results, we speculated that YVLLPSPK might modulate the mitochondrial function by promoting mitophagy to ameliorate scopolamine-induced cognitive deficiencies in mice.…”
Section: Results and Discussionmentioning
confidence: 95%
“…were efficient antioxidants with the potential to ameliorate scopolamine-treated learning and memory impairment in mice . Subsequently, we obtained 3 peptides TWLPLPR, YVLLPSPK, and KVPPLLY among peptides with molecular weight < 3 kDa and demonstrated that these could attenuate oxidative stress occurring via AKT/mTOR signaling by enhancing autophagy in Aβ 25–35 -induced neurotoxicity in PC12 cells . However, whether walnut peptides can modulate mitophagy and the mechanism by which PINK1 is involved in mitophagy remains to be discovered.…”
Section: Introductionmentioning
confidence: 99%
“…Current evidence confirmed that LAMP1 was a routinely used as a lysosome marker and closely correlated with autophagy [ 28 ]. Upregulation of LAMP1 could form autolysosomes and accelerate ROS removal, thus inhibiting oxidative stress [ 29 ]. It is well known that excessive superoxide mediated oxidative stress and autophagy plays an important role in myocardial injury [ 30 ], suggesting that LAMP1 may be a key player in cardiomyocytes.…”
Section: Discussionmentioning
confidence: 99%
“…Damaged mitochondria cause a continuous deficit to the electron transport system, resulting in the dysfunction of calcium ion homeostasis and destruction of MMP. These mitochondrial disorders limit the energy supply to neurons and eventually promote neuronal death [ 61 ]. Therefore, the protective effect of walnut against mitochondrial dysfunction in Aβ 1-42 -induced mice was confirmed, and walnut extract showed improved mitochondrial function.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, walnut ( Juglans mandshurica Maxim.) inhibits the production of mitochondrial ROS and reduces ATP content through the regulation of Akt/mammalian targets of serine/threonine protein kinase rapamycin (mTOR) signals and LC3-II/LC3-I levels in Aβ 25–35 -induced PC12 cells [ 61 ]. Therefore, similar to these results, walnut has a protective effect on mitochondrial abnormalities through ROS scavenging activity, as well as the protection of mitochondrial effects on cognitive function by improving neuronal energy metabolism.…”
Section: Discussionmentioning
confidence: 99%